Biological age in children who practise swimming - Wawrzyniak, G. (2001)
In the estimation of the developmental regularity among children it is important to know the relation between the developmental and the calendar age. It is particularly important in the estimation of the level of development among children with an increased level of guided motor activity. It takes place, for instance, in the case of children practising swimming. In auxology there are many morphological, physiological and motor features which are regarded as the measure of the developmental age. For several years researches have been conducted on the EMN index as the determinant of the biological age. The EMN index shows continuous changes during ontogeny, proves the existence of stages in the developmental age and is also considerably correlated with the calendar age. This is an ecosensitive factor. The EMN index differentiates individuals from another as well as groups isolated with regard to the effect of the environmental factors, for instance, the different levels of motor activity. The aim of this investigation is to estimate the standard of biological maturity (the body height and mass, the EMN index) among children, who went through a guided swimming training. Morphological features are most often used as the measures of development. However, they can become unreliable when they themselves establish the criterion of selection to a sports discipline or when some ranges of values are optimal on some given standards. The EMN index is not burdened with these features. The children who go through training show the higher level of the EMN index values than the children who do not go. The effect of this is the fact that young swimmers are biologically older than their peers. However, the shape of the curve of development of the EMN index in swimmers goes at a different level depending on the seniority of training. Anthropol Anz 2001 Jun;59(2):149-56